2001
DOI: 10.1046/j.1365-3024.2001.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of Encephalitozoon intestinalis, a causative agent of human microsporidiosis, in IFN‐γ receptor knockout mice

Abstract: The dissemination of Encephalitozoon intestinalis, a microsporidium causing intestinal diseases and systemic infection in humans, was investigated in IFN-gamma Ro/o mice. Although lesions were seen in organs of autopsied animals, the parasites were rarely detected using histological examination. Nevertheless, infection of the duodenum, liver, kidneys and lungs was demonstrated by polymerase chain reaction. This method also enabled the detection of the parasite in the brain and the heart. The development of E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…Se ha reportado que la inmunidad mediada por linfocitos T (LT) juega un papel importante en la defensa de la infección con microsporidios; algunos autores señalan que la respuesta inmune del hospedero contra estos parásitos es del tipo Th1 con producción de IL-2 e INFγ (8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
unclassified
“…Se ha reportado que la inmunidad mediada por linfocitos T (LT) juega un papel importante en la defensa de la infección con microsporidios; algunos autores señalan que la respuesta inmune del hospedero contra estos parásitos es del tipo Th1 con producción de IL-2 e INFγ (8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
unclassified
“…Subsequent studies confirmed the suppressive effect of IFNγ on E. cuniculi growth as well as on E. intestinalis using murine peritoneal macrophages [31] , [32] , the murine enterocyte cell line CMT-93 and human enterocyte cell line Caco-2 [33] as well as primary human monocyte-derived macrophages [34] . Furthermore, IFNγ-deficient mice are susceptible to E. cuniculi and E. intestinalis infection [32] , [35] , [36] , [37] . It is characteristic of the IRG resistance system that it is efficient in non-myeloid cells such as fibroblasts [1] , [4] , [38] .…”
Section: Resultsmentioning
confidence: 99%
“…IFN‐γ plays a major part in the immunological control of E. intestinalis and helps to prevent dissemination of the infection to other organs (9–11) but the role of the cytokine in inducing intestinal epithelium to inactivate the parasite has not been investigated. Findings in the present study indicate that IFN‐γ‐primed enterocytes may play a vital role in eliminating the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…IFN‐γ −/– or IFN‐γR −/– mice fail to control parasite reproduction effectively indicating the importance of IFN‐γ activity in control of infection (9,10). IFN‐γ is also required to prevent dissemination of E. intestinalis from the gut epithelium to other organs but how this is achieved is not known (11).…”
Section: Introductionmentioning
confidence: 99%